Dual Right Coronary Artery Associated with ASD and Pulmonary Stenosis (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Coronary artery anomalies occur in less than 1% of thecases undergoing coronary angiography, and constitute1-2% of all congenital heart disease. The origin of thecircumflex artery from the right coronary artery (RCA)or the right sinus of Valsalva is the most commonlyencountered anomaly and is usually well tolerated 2.We report the clinical , echocardiographic andangiographic findings of symptomatic 45 years elderlylady with the atrial septal defect and double rightcoronary artery and pulmonary stenosis. To ourknowledge, such associated lesion as founding this casehas not been reported in the literature till date at homeand abroad.DOI: 10.3329/jbcps.v28i2.5374J Bangladesh Coll Phys Surg 2010; 28: 125-127